2021
DOI: 10.15561/20755279.2021.0405
|View full text |Cite
|
Sign up to set email alerts
|

Examining the professional career values and career awareness of athlete- students: the sample of the faculty of sports sciences

Abstract: Background and Study Aim. Athlete-students continue their athletic careers at a professional level during their education, or many try to pursue alternative career paths. While much attention has been given to Athlete-students' academic progress and graduation rates in the literature, little attention has been paid to their attitudes towards career values and career awareness. Therefore, this study aimed to determine the career awareness and career values of athletes-students according to some demographic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Athletes are generally conscious of the fact that if they do not achieve the desired success in a competition, there will be economic losses in addition to the loss of reputation and position. While these losses show their performances in competitions, athletes are constantly exposed to the factor of psychological anxiety, even if they don't want it (Akarçeşme 2004;Han, 2009;Karamustafalıoğlu & Yumrukçal 2011;Türkçapar, 2014;Döşyılmaz & Şirin, 2021).…”
Section: öZ Yeterlilik Düzeyiyle Sınav Kaygısı Arasındaki İlişki Son...mentioning
confidence: 99%
See 1 more Smart Citation
“…Athletes are generally conscious of the fact that if they do not achieve the desired success in a competition, there will be economic losses in addition to the loss of reputation and position. While these losses show their performances in competitions, athletes are constantly exposed to the factor of psychological anxiety, even if they don't want it (Akarçeşme 2004;Han, 2009;Karamustafalıoğlu & Yumrukçal 2011;Türkçapar, 2014;Döşyılmaz & Şirin, 2021).…”
Section: öZ Yeterlilik Düzeyiyle Sınav Kaygısı Arasındaki İlişki Son...mentioning
confidence: 99%
“…cular genel manada bir yarışmada istendik başarı elde edememeleri halinde itibar ve konum kaybına ek olarak ekonomik kayıplarının olacağı konusunda bilinçlidirler. Bu kayıplar sporcularda müsabakalarda performanslarını sergilerken istemeseler de sürekli psikolojik olarak kaygı etkenine maruz kalmaktadır (Akarçeşme 2004;Han, 2009;Karamustafalıoğlu ve Yumrukçal 2011;Türkçapar, 2014;Döşyılmaz ve Şirin, 2021).…”
Section: Introductionunclassified
“…Sporcu bir yarışmayı kaybettiğinde yer ve ün kaybı ile birlikte ekonomik olarak da kayıpları olacağını bilmektedir. Bu durumun sonucu olarak sporcu, yapılan her müsabakada sahada müsabaka etmeye çıkarken kaygı yaşayarak performans sergilemek durumunda kalmaktadır (Akarçeşme 2004;Han, 2009;Karamustafalıoğlu ve Yumrukçal 2011;Spielberger ve Reheiser, 2004;Türkçapar, 2014;Döşyılmaz ve Şirin, 2021).…”
Section: Introductionunclassified
“…Sullivan and Gee's (2007) research on athletic satisfaction and communication found that as communication within the team increases, athletic satisfaction increases. Döşyılmaz and Şirin (2021) stated in their study that the role model effect of athlete leaders also contributed greatly to the career development of athletes. These studies support the idea that there is a positive relationship between leadership in sports and effective communication.…”
Section: Introductionmentioning
confidence: 99%